Conflicts between Past and Present Identity in Yahya Haqqi’s The Lamp of Umm Hashim: The Post Colonized in a Dark Passage to the Future - Fayez Refaat Abu Enein, Ghada (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to discuss mainly the changes of the main character (Ismail) in The Lamp of Umm Hashim, a novel published in 1944 by Yahya Haqqi, an Egyptian writer. Ismail, who finds himself at the crossroads of civilizations, undergoes a lot of changes due to postcolonialism and being exposed to more than one culture. The discussion will involve the relationship between education, science and faith, and societal belief in superstitions. This novel was one of the first fictional works in Arabic to deal with psychological difficulties that were faced by students returning home after being sent to Europe to complete their studies. The Lamp of Umm Hashim exposes the cultural shock that can be viewed as a post-colonial effect after being educated in Europe. The difference between East and West is explained by Dr. Edward Said in his book Orientalism, showing the clash between the cultures. This research shows the crises that face the main character while being in the center, concentrating on how Ismail deals with the changes in his self-image while he struggles with trying to belong to his Egyptian heritage.